An Investigation into the Conceptual Understanding of Students in the Light of Thinking Skills Approach - Sharma, S.V.; Yadav, S.; Rath, K.B.; Niwas, Ram; Horo, A.; Pratap, Rana (THE PRIMARY TEACHER, 2015)
A study entitled ‘An Investigation into the Conceptual Understanding of Students about the Subject Content in the Light of Thinking Skills Approach at Primary Level’ has been conducted on students of schools of experimental and control groups. Analysis of the data through both qualitative and quantitative approaches shows performance of students of experimental group is better as compared to control group in Hindi, English, EVS and Mathematics subjects. It is envisaged that teaching-thinking skills by infusing it across curricular areas may be made an integral part of teaching-learning process in today’s scenario to help students in becoming innovative problem-solvers, constructors of knowledge, thoughtful decision makers, independent thinkers and life-long learners. Present practices of designing lesson planning can be modified so as to integrate various components of thinking skills leading to create thinking classrooms